Análise proteômica da sinalização heterotípica em cultura celular de melanoma - Goncalves, Dayelle Samila Pessotti De Oliveira [UNIFESP] (2021)
The signaling events triggered by soluble mediators released from both transformed and stromal cells shape the phenotype of tumoral cells and have significant implications in cancer development and progression. In this study we performed an in vitro heterotypic signaling assay by evaluating the proteome diversity of human dermal fibroblasts after their stimulation with the conditioned media obtained from malignant melanoma cells. In addition, we also evaluated the changes in the proteome of melanoma cells after their stimulation with their own conditioned media as well as with the conditioned medium from melanoma-stimulated fibroblasts. Our results pointed out to a significant rearrangement in the proteome of stromal (Hs68) and malignant (A375) cells upon crosstalk of soluble mediators. The main proteome signature of stimulated cells was related to protein synthesis, which may indicate that this process might be an early response of stimulated stromal cells. In addition, the conditioned medium derived from ‘primed’ stromal cells (melanoma-stimulated fibroblasts) was more effective in altering the functional phenotype (cell migration) of malignant cells than the fibroblast conditioned medium alone. Collectively, self- and cross-stimulation may play a key role in shaping the tumor microenvironment and, more importantly, enable tumoral cells to succeed in the process of melanoma progression and metastasis. Although the proteome landscape of cells participating in such a heterotypic signaling represents a snapshot of a highly dynamic state, understanding the diversity of proteins and enriched biological pathways resulting from stimulated cell states may allow for targeting specific cell regulatory motifs involved in melanoma progression and metastasis.